Effects of the staging position and air−LPG mixing ratio on the combustion and emission characteristics of coal and gas co-firing. (1st September 2022) - Li, Xinzhuo; Choi, Minsung; Jung, Chanho; Park, Yeseul; Choi, Gyungmin
Abstract: Experiments were performed to study the effect of the staging air−liquefied petroleum gas (LPG) mixing ratio and staging position on the exhaust gas emissions and carbon burnout of LPG and coal under co-firing conditions. An air−LPG mixture was supplied at three ratios (10%, 20%, and 30%) to four staging positions: upstream, midstream, downstream, and below the primary combustion zone. The results showed that the combustion was unstable when the staging position was downstream of the primary combustion zone, and the highest carbon monoxide (CO) emission with standard deviation (1500 and 730 ppm, respectively) were observed at a mixing ratio of 30%. Meanwhile, supplying the air−LPG mixture at a mixing ratio of 30% and upstream of the primary combustion zone resulted in the lowest nitric oxide (NO) emission of about 134 ppm. At a mixing ratio of 10%, the mixture was instantaneously burned out at the staging position on the inner wall of the furnace, which had a negative effect on the burnout performance. The air−LPG mixing ratios of 20% and 30% staged upstream of the primary combustion zone had a synergistic effect on the reduction of CO and NO emissions and the burnout performance. Highlights: Air-LPG staging technology adjusted for a pulverized coal- and gas-fired furnace. Effects of LPG stoichiometric ratios on exhaust emissions were evaluated. Minimum NO emission is 165.5 ppm when the stoichiometric ratio of LPG is 1.0. Air-LPG ratio of 30% and staging upstream the flame reduced NO emission by 18%. Eco-friendly combustion and fuel flexibility are proposed in co-fired power plants.